Patterns of Geographical and Potential Adaptive Divergence in the Genome of the Common Carp (Cyprinus carpio) - Xu, Jian; Jiang, Yanliang; Zhao, Zixia; Zhang, Hanyuan; Peng, Wenzhu; Feng, Jianxin; Dong, Chuanju; Chen, Baohua; Tai, Ruyu; Xu, Peng (Frontiers in Genetics, 2019)
The common carp, Cyprinus carpio, is a cyprinid fish species cultured in Europe and Asia. It accounts for > 70% of freshwater aquaculture production worldwide. We conducted a population genomics analysis on C. carpio using high-throughput SNP genotyping of 2,198 individuals from 14 populations worldwide to determine the genetic architecture of common carp populations and the genetic bases for environmental adaptation. Structure analyses including phylogeny and principal component analysis were also conducted, showing distinct geographical patterns in European and Asian populations. The linkage disequilibrium block average lengths of the 14 populations ranged from 3.94 kb to 36.67 kb. Genes within selective sweep regions were identified by genome scanning among the different populations, including gdf6a, bmpr1b, and opsin5. Gene ontology and KEGG enrichment analyses revealed potential trait-related loci and genes associated with body shape, scaling patterns, and skin color. This population genomics analysis may provide valuable clues for future genome-assisted breeding of C. carpio.